Was technological change in the early Industrial Revolution Schumpeterian? Evidence of cotton textile profitability - Harley, C (2012)
Price and profit data between the 1770s and the 1820s from accounting records of three Lancashire cotton firms help to illumine the nature of the economic processes at work in early industrialization. Many historians have seen the Industrial Revolution as a Schumpeterian process in which discontinuous technological change led by the mechanized factories of the cotton industry created large profits for innovators that persisted in succeeding decades while technology slowly diffused. In this view imperfect capital markets limited the use of the new technology, keeping profits high. Reinvestment of these profits gradually financed expansion of innovating firms. The new technology dominated only after a long diffusion process. The evidence here, however, supports a more equilibrium view in which the industry expanded rapidly and prices fell in response to technological change. Expansion of the industry led to dramatic declines in the prices of cotton goods as early as the 1780s. There is no evidence of super-normal profits thereafter. Prices continued to fall and output expand thereafter as cost-reducing technological change continued. © 2012 Elsevier Inc.